Dysfunction of Protein Quality Control in Parkinsonism–Dementia Complex of Guam - Verheijen, Bert M.; Oyanagi, Kiyomitsu; van Leeuwen, Fred W. (Frontiers in Neurology, 2018)
Guam parkinsonism-dementia complex (G-PDC) is an enigmatic neurodegenerative disease that is endemic to the Pacific island of Guam. G-PDC patients are clinically characterized by progressive cognitive impairment and parkinsonism. Neuropathologically, G-PDC is characterized by abundant neurofibrillary tangles (NFTs), which are composed of hyperphosphorylated tau, marked deposition of 43-kDa TAR DNA-binding protein (TDP-43) and neuronal loss. Although both genetic and environmental factors have been implicated, the etiology and pathogenesis of G-PDC remain unknown. Recent neuropathological studies have provided new clues about the pathomechanisms involved in G-PDC. For example, deposition of abnormal components of the protein quality control (PQC) system in brains of G-PDC patients indicates a role for proteostasis imbalance in the disease. This opens up promising avenues for new research on G-PDC and could have important implications for the study of other neurodegenerative disorders.